Akal dan Wahyu Dalam Diskursus Filsafat Pendidikan Islam (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
This paper discusses the issues of mind and revelation that are examined based on the philosophy of Islamic Education. It is examined by running three steps. First, collecting primary and secondary data; second, clarifying all the important elements and analyzing the data; third, presenting the real movement which is the conception of mind and revelation. Based on these stages of work, the writer utilized three methods of study. First, content analysis method to analyze the content of the text; second, descriptive interpretation to interpret books; third, historical and philosophical method, that is reviewing the historical and social context, religion, politics and philosophy. Looking at the epistemological framework coming from the authoritative of mind and revelation and history, either the classic or the modern one optimizes the function of revelation in all aspect of life, either in educational reality or in knowledge of morality, human, and God.